Instrumentalne wykorzystywanie władzy sędziowskiej po wyroku TSUE – wieloaspektowa analiza legalnej korupcji - Walczak, Waldemar (Studia Prawa Publicznego, 2020)
The article presents considerations and multifaceted analyses of the conditions and motives of judicial decisions taken after the judgment of the TSUE 19 November 2019, in the context of how Poland’s judiciary system functions. It begins by explaining how to perceive and understand the essence of legal corruption in terms of the use of law, power and professional position. The possibilities of the intentional use of judicial power for specific needs and purposes is discussed in this context. The next part of the paper is devoted to a critical analysis of selectively interpreted right to a tribunal enshrined in art. 45 of the Polish Constitution in connection with other values enshrined therein. The right of every citizen to a fair and public hearing of their case, without undue delay by a competent, independent, impartial and independent court, is presented in terms of the constitutional perspective, the principle of equal treatment and non-discrimination. The problem outlined here is considered from the point of view of protection against the arbitrariness of authorities and the possibility of appealing against personnel decisions enabling employment to be taken up in selected positions in state institutions. Attention is paid to the privileged legal position of judges over other citizens. The issues described and the arguments presented in this article are entirely overlooked in the literature, as well as in public debate. What follows is an explanation of how TSUE rulings are interpreted differently by various public authorities. Reference is also made to the dictum of the Supreme Court judgment of 5 December 2019, which was issued in its Labour Law and Social Security Chamber. That process initiated specific actions and activities taken by individual groups of Supreme Court judges. Finally, the resolution of the combined three chambers of the Supreme Court on 23 January 2020, the judgment of the Constitutional Tribunal of 20 April 2020, and divergent decisions regarding the implementation of the TSUE’s position of 8 April 2020 are discussed.